Effectiveness of Monetary Policy Transmission Through Sharia and Conventional Instruments in Influencing Inflation in Indonesia - Ishak, Ishak; Aqidah, Nur Ariani; Rusydi, Mikdar (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study investigates the influence of the transmission of monetary policies through the Sharia and Conventional monetary policy instruments on Indonesian inflation using data analysis techniques such as the Vector Error Correction Model (VECM). The data of this study was obtained from financial statements of the Annual Report of Indonesian Economic and Financial Statistics (2016 to 2020), Consumer Price Index (CPI) data taken from the Central Bureau of Statistics (BPS; 2016 to 2020), from Banking Statistics Annual Reports (2016 to 2020), and from the Islamic Banking Statistics Annual Reports (2016 to 2020). The test results on the sharia instrument indicators show a negative reaction of the Consumer Price Index to shocks in FINC and SBIS, but a positive reaction to shocks in third-party funds and Islamic interbank money market. According to the test results on the conventional instrument indicators, the Consumer Price Index responds negatively to shock in LOAN, DPK, and SBI, and positively to shocks in PUAB.